Integrated Islamic School Education Model (1980-1998) - Pribadi, Joko; Ansori, M Afif; Andari, An An; Sugianto, Sugianto; Rosmawati, Rosmawati (Yupa: Historical Studies Journal, 2024)
Islamic education in Indonesia has experienced rapid development alongside the growth of the Muslim population. This paper discusses the role of Integrated Islamic Schools (IIS) as a new trend in Islamic education in Indonesia. This article analyzes the historical development of Islamic education, the role of IIS in facing the challenges of modernization, and its impact on Indonesian Muslim society. In the context of the development of Islamic education, there has been significant transformation during the reform era, including changes in the national education system. Islamic education is no longer confined to traditional models, and the emergence of IIS in several major cities marks a step towards the modernization of Islamic educationThis article employs a qualitative descriptive research method focusing on data analysis from various sources, including books, journals, and relevant publications. The research findings indicate that IIS, as part of the Integrated Islamic Schools Network of Indonesia, has attracted public attention, especially in major cities. Despite the high cost of education, IIS is considered an alternative Islamic education that combines Islamic values with a modern approach.